THE EFFECTIVENESS OF THE CCL (COLLABORATIVE CREATIVITY LEARNING) LEARNING MODEL ON THE SCIENTIFIC CREATIVITY OF STUDENTS IN CLASS VIII OF JUNIOR HIGH SCHOOL - Erliana, Icha; Singgih, Suwito; Juliyanto, Eko (Universitas Tanjungpura, 2024)
The aim of this study for analyze the effectiveness of the Collaborative Creativity Learning (CCL) learning model on increasing scientific creativity class VIII junior high school students. The research method used is quasi- experimental quantitative research with Non-equivalent Control Group Design. The research population is all class VIII students at SMPN 2 Magelang, with class VIII G as the control group and class VIII F as the experimental group. The research instrument is: test the description has been validated and validated in a way reliable. The results of data analysis show an increase in scientific creativity in each indicator after given treatment, with experienced indicators enhancement the highest in the experimental class is Real advanced and Technical production. The conclusion of this research shows that the application of the CCL learning model is effective in increasing scientific creativity students, this is supported by the significant results of the Independent Sample t-test.